The continuous strength method for the design of high strength steel tubular sections in compression. (1st May 2018) - Lan, Xiaoyi; Chen, Junbo; Chan, Tak-Ming; Young, Ben
Highlights: A dataset of 277 existing tests on CHS, EHS, SHS and RHS stub columns was collated. A numerical study on 465 high strength steel (HSS) stub columns was conducted. Continuous strength method (CSM) was extended for the design of HSS tubular sections in compression. The proposed CSM can produce accurate and consistent strength predictions. Abstract: This paper aims to extend the deformation-based design method named continuous strength method (CSM) for the design of high strength steel tubular sections in compression. The CSM employs a base curve relating the cross-section resistance to its deformation capacity and adopts an elastic, linear hardening material model. Non-slender and slender circular hollow sections (CHS), elliptical hollow sections (EHS), square hollow sections (SHS) and rectangular hollow sections (RHS) were investigated in this study. Hot-finished, cold-formed and built-up steel tubular sections with yield stresses up to 1405 MPa were covered. An extensive numerical study was carried out to supplement the limited test results of high strength steel stub columns in the literature. The cross-section resistances obtained from the proposed CSM, the direct strength method (DSM), and design methods in EN 1993-1-5, EN 1993-1-6, ANSI/AISC 360-10 and AISI S100 were compared with the experimental and numerical capacities of 742 stub columns. It is shown that the proposed CSM can produce more accurate and less scattered strength predictions than the current DSM and design codes.